DISTRIBUSI MONYET EKOR PANJANG (Macaca fascicularis) DI TAMAN NASIONAL WAY KAMBAS - Nidya Astrida Ziyus; Agus Setiawan; Bainah Sari Dewi; Sugeng Prayitno Harianto (Jurnal Belantara, 2019)
Long-tailed macaque (Macaca fascicularis) is one of the forest-dwelling animals. Long-tailed monkeys can be found along the road that connects the green signpost with elephant training center. The aim of research to determine the spread of long-tailed monkeys in the area.  The research methods used Concentration Count on points discovery of groups of long-tailed monkeys.  An observation method used to determine the area of long-tailed monkeys move is done by taking the coordinates of the GPS based outer canopy that is used to move. Habitat conditions are determined using the Rapid Assessment. The results obtained in such a location that there are five groups of long-tailed monkeys who are geographically separated from each other. Fifth habitat conditions are relatively similar groups dominated by rosewood and main feed jeluak, hibiscus and islands. Three groups of five of the group activities occur near Entrance PLG. It shows that the group is influenced by tourist activity. Two other groups are in the natural habitat conditions.